Para pensar arte, educação e sustentabilidade: um estudo do Projeto Respiradores pela ótica das noções de ecosofia e educação performativa - Francisco de Paulo D'Avila Júnior (2023)
This master's thesis analyzes the artistic-pedagogical project Respiradores, developed at the Bernardo Valadares de Vasconcellos State School, Sete Lagoas-MG, with students from Elementary School II, based on the following concepts: ecosophy and performative education. The research explores how these elements intertwine to promote a global approach to cultural, emotional and environmental aspects in the teaching-learning process. The impacts of this perspective on students' training, their perception of the environment and the development of creative, critical and civic skills are involved. Furthermore, examine how artistic performance can be an effective strategy to engage students in a participatory and reflective way in environmental and social issues in art classes and in the school context.